Internet Access And Utilization Among Medical Undergraduate and Post Graduate Students of a Medical College In Madhya Pradesh - Chhari Neeraj; Chakole Swarupa (Medsci Publications, 2015)
Background: Use of computerized information systems by medical professionals can improve the quality of care, enhance the use of evidence-based treatment, and maintain and update knowledge. Aim of this study was to evaluate the pattern of internet access and utilization by medical students in Ujjain. Methods: Cross sectional study conducted on all undergraduate & post graduate. Open -ended semi-structured questionnaire was used. Results: A total of 507 UG & 127 PG students were approached and 386(76%) UG, 119(93%) PG's completed the questionnaires. Majority of the respondents (87.0%) reported having knowledge of internet use. About 365(72%) of the study subjects own computer, being significantly higher among PG's (89%0 as compared to UG's (67%).Main purpose of using internet as cited by UG's was email/chatting (74%), where as dissertation work was main purpose among PG (66%).Slow speed of internet was the main problem faced by the subjects 299(595) while accessing the website. Conclusion: Majority of the medical students in this study had access to internet and were using it for both academic and personal reasons. Students should be trained to extract valuable information from the special medical web sites and should be encouraged to check the authenticity of information by correlating with existing evidences.